Hubungan Tingkat Pengetahuan dengan Pola Makan Aktivitas Fisik dan Peran Serta Orang Tua Anak Obesitas Di SD Saraswati 5 Denpasar - Ni Made Yeni Meilasanti; AA Gde Raka Kayanaya; I Komang Agusjaya (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2019)
Childhood obesity is a serious public health problem in the 21st century. This is a global problem in low- and middle-income countries. The risk factors of childhood obesity are knowledge level, children’s dietary patterns, physical activity, and the role of parents. This study aims to observe the association between children’s dietary patterns, physical activity, and the role of parents with childhood obesity in Saraswati 5 Denpasar elementary schools. Method. This is a cross-sectional analytical study. Data obtained from the questionnaire are distributed to the child and the parents. Result. There were 64 children taken as subjects of the study who were obese from grade 1 until grade 5. The results obtained for all variables are categorized into 3 categories that are good, enough, and less. For the research result, there were 23 samples (53,5%) in the good category, 12 samples (27,9%) in enough category, and 8 samples (18,6%) in the less category. For the result of the research on the sample diet, there were 21 samples (48,8%) in the good category, 13 samples (30,3%) sufficient category, and 9 samples also (20,9%) less category. For the result of research on the physical activity of the sample, there were 9 samples (20,9%) good category, 14 samples (32,6%) in the enough category, and 20 samples (46,5%) in the less category. For the parents' role, there was 1 sample (2,3%) in either category, 4 samples (9,3%) insufficient category, and 38 samples (88,4%) in the less category. The analysis data resulted that knowledge level was associated with children's dietary patterns (p=0,050) and also knowledge level was associated with the role of parents (p=0,036) and also knowledge level was associated with physical activity (p=0,031). Conclusion. There is an association between knowledge level with a dietary pattern, physical activity, and the role of parents with childhood obesity in Saraswati 5 Denpasar elementary schools. Keywords: Childhood obesity, knowledge level, dietary pattern, physical activity, the role of parentsChildhood obesity is serious public health problem at 21st century. This is the global problem in low- and middle-income countries. The risk factors of childhood obesity are knowledge level, children’s dietary pattern, physical activity, and the role of parents. This study aims to observe the association between children’s dietary pattern, physical activity, and the role of parents with childhood obesity in Saraswati 5 Denpasar elementary schools. Method. This is a cross sectional analitical study. Data obtained from the questionnaire which are distributed to child and the parents. Result. There were 64 children taken as subjects of study were obesity from grade 1 until grade 5. The results obtained for all variables are categorized into 3 categories that is good, enough, and less. For the research result, there were 23 samples (53,5%) in good category, 12 samples (27,9%) in enough category, and 8 sample (18,6%) in the less category. For the result of the research on the sample diet, there were 21 samples (48,8%) in good category, 13 samples (30,3%) sufficient category, and 9 samples also (20,9%) less category. For the result of research on the physical activity of the sample, there were 9 samples (20,9%) good category, 14 samples (32,6%) in enough category, and 20 samples (46,5%) in less category. For the parents' role there were 1 samples (2,3%) in either category, 4 samples (9,3%) in sufficient category, and 38 samples (88,4%) in the less category. The analysis data resulted that knowledge level was associate with childrens’s dietary pattern (p=0,050) and also knowledge level was associate with  role of parents (p=0,036) and also knowledge level was associate with physical activity (p=0,031). Conclusion. There is association between knowledge level with dietary pattern, physical activity, and role of parents with childhood obesity in Saraswati 5 Denpasar elementary schools.  Keywords:Childhood obesity, knowledge level, dietary pattern, physical activity, role of parents.